Bahia-Minas railroad: remaining materialities in the landscape of the municipality of Teófilo Otoni, Minas Gerais (Revista Espinhaço, 2022)
The Bahia-Minas Railroad (EFBM) has great importance in the popular imagination of the municipality of Teófilo Otoni-MG. Despite this, more than half a century aer its decommissioning, there are no organized public records on the railway operations in the municipality, nor the conservation of materials that refer to the old “Bahiminas”, currently pulverized in private collections. Supported by theoretical-methodological bases of Historical Geography, this article aims to contribute to the systematization and mapping of the architectural reminiscences of the railway in Teófilo Otoni and to assess its conservation conditions. To this end, field work was carried out for data collection, which were organized using geotechnologies in a geovisualization platform that allows the visual and interactive reading of the identified railway heritage. It was possible to catalog 21 structures, such as railway stations, bridges, tunnels, class houses, locomotive and other buildings that date back to the times of the Bahia-Minas Railway operation. However, we verified that the conservation conditions of the railway heritage are precarious in the municipality, demanding public policies for the conservation and valorization of the materials that still exist.
Keywords: geovisualization; material heritage; railway; northeast of Minas Gerais